2014
DOI: 10.1002/adma.201403115
|View full text |Cite
|
Sign up to set email alerts
|

Ferroelectricity in Si‐Doped HfO2 Revealed: A Binary Lead‐Free Ferroelectric

Abstract: Static domain structures and polarization dynamics of silicon doped HfO2 are explored. The evolution of ferroelectricity as a function of Si-doping level driving the transition from paraelectricity via ferroelectricity to antiferroelectricity is investigated. Ferroelectric and antiferroelectric properties can be observed locally on the pristine, poled and electroded surfaces, providing conclusive evidence to intrinsic ferroic behavior.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
110
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 156 publications
(117 citation statements)
references
References 26 publications
4
110
0
Order By: Relevance
“…3 Martin et al also examined the origin of the wakeup effect in Si:HfO 2 films based on HRTEM analysis and reported that the partial phase transition from the m-to o-phase was the reason for the wake-up effect. 5 In the current work, it is also believed that the redistribution of charged defects, such as oxygen vacancies or m-to o-phase transition, might be caused due to the increase in P r and E c during the wake-up process. On the other hand, the E int , which can be calculated by averaging the positive and negative E c values, also changed during the wake-up field cycling.…”
Section: Resultsmentioning
confidence: 97%
“…3 Martin et al also examined the origin of the wakeup effect in Si:HfO 2 films based on HRTEM analysis and reported that the partial phase transition from the m-to o-phase was the reason for the wake-up effect. 5 In the current work, it is also believed that the redistribution of charged defects, such as oxygen vacancies or m-to o-phase transition, might be caused due to the increase in P r and E c during the wake-up process. On the other hand, the E int , which can be calculated by averaging the positive and negative E c values, also changed during the wake-up field cycling.…”
Section: Resultsmentioning
confidence: 97%
“…Higher activation value of the transformation rate into the m-phase for PMA samples clearly demonstrates that the TiN capping layer posed a higher activation energy barrier upon t-to-m phase transformation. [43,44] To sum up, both the JMA and NLT models effectively showed that the capping layer generated a higher kinetic energy barrier and hampered the nucleation of the m-phase within HZO thin film. [5][6][7][8][10][11][12][39][40][41][42] Compared to the reported activation energy value of 1.2 eV f.u.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, ferroelectricity can also be achieved in HfO 2 -ZrO 2 solid-solution [2]. Apart from macroscopic polarization/strain hysteresis measurements and micro-structural analyses of the phase transition, conclusive evidences for the existence of intrinsic ferroic behavior have also been provided by mesoscopic piezoresponse force microscopy (PFM) experiments [3] and first principles calculation [4][5][6][7].…”
Section: Introductionmentioning
confidence: 98%